Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
World Tribology Congress III, Volume 1 2005
DOI: 10.1115/wtc2005-63562
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Material Property on Micropitting and Pitting Behavior

Abstract: Recent studies have shown that micropitting initiated pitting appears to be the dominant metal fatigue mode in modern bearings and gears. If the formation of micropits can be controlled, the fatigue life of the bearings and gears can be readily lengthened, so the useful life of the engine or transmission can be radically extended. The lack of in-depth understanding of micropitting initiation mechanism hinders progress to control the micropitting-initiated pitting failure mode. In this study, we explore the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As revealed by various experimental observations [28][29][30], the difference of gear steel materials and the heat treatment process could generate distinguished micropitting resistances. As reported in the Reference [31], high strength austempered ductile iron gears were gradually accepted due to the low production cost, the eventual noise and vibration reduction, and the self-lubricant properties through graphite nodules, resulting in remarkable gear tooth flank capacity.…”
Section: Gear Materials and Macroscopic Geometriesmentioning
confidence: 99%
“…As revealed by various experimental observations [28][29][30], the difference of gear steel materials and the heat treatment process could generate distinguished micropitting resistances. As reported in the Reference [31], high strength austempered ductile iron gears were gradually accepted due to the low production cost, the eventual noise and vibration reduction, and the self-lubricant properties through graphite nodules, resulting in remarkable gear tooth flank capacity.…”
Section: Gear Materials and Macroscopic Geometriesmentioning
confidence: 99%
“…Martensite decay in bearings has been amply investigated and excellent reviews can be found in [5,6]. There are fewer published reports on martensite decay in gears [3,[7][8][9][10][11][12][13][14][15][16][17][18] but they all describe dark and/or white etching features as in bearings. A major difference between martensite decay in bearings and martensite decay in gears is the location where the transformation occurs.…”
Section: Introductionmentioning
confidence: 99%